Adapting Fiscal Policies for Regional Growth: Educational Insights from Situbondo’s Tax Revenue - Moh Rasidi; Sofiyatun Amiliyah (Journal of Educational Management Research, 2025)
This study aims to determine the tax revenue from the Land and Building Acquisition Fee (BPHTB) and its contribution to increasing Regional Original Income (PAD) in Situbondo Regency from 2022 to 2024. The research employs a descriptive qualitative method, collecting data through interviews, observations, and documentation. The results show that the contribution of BPHTB to PAD in Situbondo Regency has declined over the years. In 2022, it contributed 29.19%, decreasing to 26.06% in 2023, and further to 24.31% in 2024. This downward trend indicates the need for more adaptive fiscal policy strategies to optimize BPHTB revenue as a regional income source. Theoretically, this study provides important implications for the field of education, particularly in economics and public policy education. It offers a real-world understanding of the significance of local tax optimization in regional development. Additionally, the findings can serve as learning material in public economics or regional financial management courses, helping students understand the role of taxation in supporting sustainable regional growth.